Monitoring and evaluation of the recruitment and selection practices in the Lesotho public service - Makiti, Mathabo Annacletta (University of the Free State, 2017)
The study examined the implementation of monitoring and evaluation of the Human Resources policies by the Lesotho Ministry of Public Service, specifically the Recruitment and Selection Policy. The Ministry of Public Service has a mandate of ensuring appropriate implementation of the recruitment and selection practices across the public service. However, the final selection is authorised by the Public Service Commission. The commission is “an independent agency in the conduct of its business and is committed through legal frameworks to safeguard the merit principle”. The study investigated how the Commission and the Ministry of Public Service can collaborate on monitoring and evaluation of the recruitment and selection processes. Lesotho Wage Bill has been classified as the one of the highest in the world. For this reason, the Government of Lesotho has put forward administrative reforms to resize and restructure the Public Service. Evidence provided in the World Bank Reports is that the Public Service is bottom heavy with low-skilled staff exceeding skilled and professional employees. The reports also state that the Government is failing to put its skilled workforce to good use, as some public servants are employed above their level of expertise. The study therefore extensively discusses the concepts of monitoring and evaluation as management principles that could be implemented internally by management in the Ministry of Public Service to ensure that appropriate recruitment and selection practices are executed within the Ministry and across the line ministries. Throughout the study, Monitoring and Evaluation were explained as separate, but complementary concepts. It is therefore established, based on the document analysis and interviews conducted with the Public Service officials in the Ministry of Public Service (Human Resource Department) and the Public Service Commission, that lack of effective monitoring and evaluation procedures, as well as political interference in the recruitment and selection processes of the public service are attributed to the recruitment and selection irregularities. The study provides recommendations with regard to the interviews conducted, the document analysis and the literature reviewed.
Dissertation (M.P.A. (Public Administration and Management))--University of the Free State, 2017
Keywords: Public administration; Monitoring; Evaluation; Ministry of public service; Public sector; Human resource management; Recruitment; Selection; Efficient; Effective